The Impact of Population Aging on Economic Development in Vietnam - Bui, Tu Ngoc; Tran, Trang Mai (Darul Yasin Al Sys, 2023)
Population aging has an impact on many socio-economic aspects of each country. Population aging will also create many challenges for Vietnam, especially growth issues, labor supply and productivity, social security and health care systems, and pension funds. and social problems arise. The transition time from an aging population to an aging population in Vietnam is faster than in other countries, and especially when Vietnam is still a developing country with a low, middle income, these challenges are even more difficult for the economy. This article will evaluate the impacts of population aging in Vietnam on socioeconomic development and provide some policy suggestions for Vietnam's development process.